Heat Adaptation and Nutrition Practices: Athlete and Practitioner Knowledge and Use - Alabdulwahed, Salma; Galán-López, Natalia; Hill, Tom; James, Lewis J; Chrismas, Bryna Catherine Rose; Racinais, Sebastien; Stellingwerff, Trent; Leal, Diogo V; Hausen, Matheus; Chamari, Karim; Fullagar, Hugh H K; Esh, Christopher; et al. (International journal of sports physiology and performance, 2022)
To survey elite athletes and practitioners to identify (1) knowledge and application of heat acclimation/acclimatization (HA) interventions, (2) barriers to HA application, and (3) nutritional practices supporting HA. Elite athletes (n = 55) and practitioners (n = 99) completed an online survey. Mann-Whitney U tests (effect size [ES; r]) assessed differences between ROLE (athletes vs practitioners) and CLIMATE (hot vs temperate). Logistic regression and Pearson chi-square (ES Phi [ϕ]) assessed relationships. Practitioners were more likely to report measuring athletes' core temperature (training: practitioners 40% [athletes 15%]; P = .001, odds ratio = 4.0, 95% CI, 2%-9%; competition: practitioners 25% [athletes 9%]; P = .020, odds ratio = 3.4, 95% CI, 1%-10%). Practitioners (55% [15% athletes]) were more likely to perceive rectal as the gold standard core temperature measurement site (P = .013, ϕ = .49, medium ES). Temperate (57% [22% hot]) CLIMATE dwellers ranked active HA effectiveness higher (P < .001, r = .30, medium ES). Practitioners commonly identified athletes' preference (48%), accessibility, and cost (both 47%) as barriers to HA. Increasing carbohydrate intake when training in the heat was more likely recommended by practitioners (49%) than adopted by athletes (26%; P = .006, 95% CI, 0.1%-1%). Practitioners (56% [28% athletes]) were more likely to plan athletes' daily fluid strategies, adopting a preplanned approach (P = .001; 95% CI, 0.1%-1%). Practitioners, and to a greater extent athletes, lacked self-reported key HA knowledge (eg, core temperature assessment/monitoring methods) yet demonstrated comparatively more appropriate nutritional practices (eg, hydration).